PENGARUH KOMPONEN RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, CAPITAL) TERHADAP RETURN SAHAM SEKTOR PERBANKAN Studi Pada Bursa Efek Indonesia - Yuliarti Rezeki; Fifi Swandari; Abdul Hadi (Universitas Lambung Mangkurat, 2017)
The purpose of this research is to analyze the influence of RGEC Components ie Non Performing Loans, Interest Rate Risk, Loan To Deposit Ratio, Institutional Ownership, Proportion of Independent Commissioner, Audit Committee, Return on Asset, Net Interest Margin and Capital Adequacy Ratio to stock return. The analysis test used is multiple linear regression analysis. The population used by banking companies listed in Indonesia Stock Exchange period 2011-2015 period and which meet the criteria of sample selection. The sample used is 23 companies. Data are collected through secondary data collection in the form of company annual report for 2011-2015 period published in Indonesia Stock Exchange. The research hypothesis was tested by multiple linear regression that has met the classical assumption test. The result of analysis shows that Non Performing loan, Interest Rate Risk, Proportion of Independent Board of Commissioner, Net Interest Margin and Capital Adequacy Ratio have no significant effect on stock return while Loan To Deposit Ratio, Institutional Ownership, Audit Committee, and Return on Asset have significant effect to return stock.